Evaluación de los niveles de ruido ambiental en las principales zonas comerciales de la ciudad de trujillo durante el periodo noviembre 2016 - febrero 2017 - Azañedo Obando, Lizeth Andrea (2017)
The present research tries to focus on one of the many environmental impacts that is currently experienced: Sound pollution, and is limited to evaluate the most important commercial areas of the city of Trujillo, in turn analyze the noise caused by the density of Vehicular flow, as the main polluting activity generated by man. These results were compared with the Peruvian Standards in force in this case with the Environmental Noise Quality Standards approved by D.S.085-2003-PCM. To carry out this study, and to carry out the appropriate procedures, the National Environmental Noise Monitoring Protocol was taken as a guide. Six commercial areas to be evaluated were selected: Real Plaza, Mall Plaza, and The Viceroy shopping center, Central Market, Zonal Market Palermo and Association of Small Industrialists and Artisans of Trujillo. The monitoring was carried out on several days of the week (Thursday to Sunday) and within what corresponds to the daytime set in the Regulation for noise mentioned above (07:01 – 22:00 hours). In each area to be evaluated the stations were mounted and measured for a period of 15 minutes for each point. Finally, the results obtained were compared with the Standards mentioned above, which should not exceed 70 dB. It was possible to conclude that more than 50% of the results of all the evaluated zones, surpasses the ECAs for noise, being the Zone Market Palermo one of the zones most affected due to the absence of environmental conscience of the conductors